Sustained Recovery in a Treatment-Refractory Obsessive–Compulsive Disorder Patient After Deep Brain Stimulation Battery Failure - Maatoug, Redwan; Valero-Cabré, Antoni; Duriez, Philibert; Saudreau, Bertrand; Fernández-Vidal, Sara; Karachi, Carine; Millet, Bruno (Frontiers in Psychiatry, 2020)
Obsessive-compulsive disorder (OCD) is a widespread chronic neuropsychiatric disorder characterized by recurrent intrusive thoughts, images, or urges (obsessions) that typically cause anxiety or distress. Even when optimal treatment is provided, 10% of patients remain severely affected chronically. In some countries, deep brain stimulation (DBS) is an approved and effective therapy for patients suffering from treatment-resistant OCD. Hereafter, we report the case of a middle-aged man with a long history of treatment-resistant OCD spanning nearly a decade with Y-BOCS scores oscillating between 21 and 28. The patient underwent bilateral implantation of ventral striatum/ventral capsule (VS/VC) DBS leads attached to a battery-operated implanted pulse generator (IPG). After a 3 months post-implantation period the DBS protocol started. Three months after the onset of DBS treatment, the patient’s Y-BOCS score had dropped to 3 and he became steadily asymptomatic. Yet inadvertently, at this time, it was found out that the IPG battery had discharged completely, interrupting brain stimulation. The medical team carried on with the original therapeutic and evaluation plan in absence of active DBS current. After 12 additional months under off-DBS, the patient remained at a Y-BOCS score of 7 and asymptomatic. To our knowledge, this is the first report which provides an opportunity to discuss four different hypotheses of long-term recovery induced by DBS in a treatment-refractory OCD patient, notably: (1) A placebo effect; (2) Paradoxical improvements induced by micro-lesions generated by DBS probe implantation procedures; (3) Unexpected late spontaneous improvements; (4) Recovery driven by a combination of active DBS-induction, the effects of medication and DBS-placebo effects.